[tex]\frac{ds}{dt}=600-\frac{2s}{200+t}[/tex](adsbygoogle = window.adsbygoogle || []).push({});

[tex]\frac{ds}{dt}+\frac{2s}{200+t}=600[/tex]

[tex]\frac{ds}{dt}e^{ln(100+t/2)}+\frac{2s}{200+t}e^{ln(100+t/2)}=e^{ln(100+t/2)}600[/tex]

[tex]\frac{d}{dt}(se^{ln(100+t/2)})=(100+t/2)600[/tex]

[tex]se^{ln(100+t/2)}=\int(100+t/2)600dt[/tex]

[tex]s(100+t/2)=600(100t+t^2/4)+C[/tex]

t=0 s=20 000

[tex]20.000\cdot100=C[/tex]

But this is wrong

I guess i want to know what I did wrong. I used the product rule for derivation backwards. Here is answer sheet

http://bildr.no/view/1051423

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Differential equation

**Physics Forums | Science Articles, Homework Help, Discussion**